Immunological Implications of Gold Weight Implantation for Lagophthalmos: A Systematic Review - Iskandar, Elza; Krisna Murti; Irsan Saleh; Ramzi Amin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Gold weight implantation is a well-established surgical intervention for lagophthalmos, a condition characterized by incomplete eyelid closure. While generally safe and effective, gold implants can elicit immune responses, potentially leading to complications. This systematic review aims to comprehensively evaluate the immunological implications of gold weight implantation in lagophthalmos treatment. Methods: A systematic search of PubMed and ScienceDirect databases was conducted, encompassing studies published from 2000 to June 2024. Keywords included "gold weight implant" and "gold implant AND eyelid." Studies reporting quantitative data on immune responses to gold implants were included. Data extracted included study design, patient demographics, implant characteristics, follow-up duration, complications, and long-term outcomes. Results: Thirteen studies met the inclusion criteria, encompassing a total of 340 patients (370 eyelids). Reported complications included hypersensitivity reactions (11.9%), lymphoma (0.6%), infection (1.2%), extrusion (8.1%), and nonspecific inflammatory reactions (4.3%). Hypersensitivity reactions were mediated by T-cell and B-cell responses, leading to chronic inflammation. Lymphoma cases highlighted the potential for chronic inflammation to trigger lymphoproliferative disorders. Infections were infrequent but could necessitate implant removal. Extrusion rates varied, influenced by implant size and placement. Nonspecific inflammatory reactions were observed, often requiring implant removal or steroid treatment. Conclusion: Gold weight implantation can trigger diverse immune responses, ranging from mild inflammation to severe hypersensitivity and lymphoma. Careful patient selection, meticulous surgical technique, and vigilant postoperative monitoring are crucial to minimize complications. Further research is warranted to elucidate the precise mechanisms underlying these immune responses and develop strategies for their prevention and management.